Estudio diagnóstico de la carpeta asfáltica para la comparación entre pavimentos rígidos y flexibles como alternativa de uso para el parqueadero común de la carrera 14a #27a-57 sur, en Bogotá - Pinzón Forero, Hilton Miguel (Universidad Antonio Nariño, 2023)
In this document we want to answer the questions proposed for the parking lot located in Carrera 14ª #27 a – 57 yes, is a flexible asphalt or a rigid one effective? This seen from the economic factor, initially a visual diagnosis of the asphalt folder using the Invias manual for this purpose, then a rigid pavement design is elaborated because the flexible pavement design already exists in one of the annexes, continuing with the process, the calculations related to the intervention area are made, the amount of materials required for the designs of rigid and flexible pavement then the budget is prepared based on the amount of materials required, continuing the calculation of the budgets required for the maintenance of flexible pavement since for rigid pavement they are not required, Finally, the total costs required to keep the two types of pavement in operation for 25 years are added, which is the time for which were designed, resulting in the rigid pavement being the most effective seen from the economic factor